Molise, una proposta di Marketing Culturale per lo Sviluppo del Territorio - Montereale, Lia (Archeomatica, 2021)
This document is divided into four sections. The first section, the introduction, analyses the transformations that the cultural sector has been undergoing in recent years and the new interest towards forms of slow tourism, traditions and little medieval villages. The second section describes the territory and its criticalities. The third section shows the strategy and the proposed actions to increase the flow of tourists and the economic growth of Molise. The fourth section is dedicated to the conclusions and summarizes the main points of the topics covered.